MEDIA PEMBELAJARAN SISWA TAMAN KANAK-KANAK MENGGUNAKAN ANIMASI FLASH - Imam Rosyadi; Fera Arzakiyah (Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
Student Learning Kindergarten generally still use Viewer tool where students has usually been introduced by first objects that are exist around themes based on the existing school, then students has been introduced by figures, letters, and then learn to count. Based on the problems in kindergarten about the learning process it still doing by monotonous teacher explain ation suich as that the introduction of numbers, letters and learn to count only through books. So that students easily bored and lack of understanding regarding the introduction of numbers, letters and learn to count. Because, there are many students but teacher so that the students may and doing anyting, so that are therefore needed Media Student Learning Kindergarten Using Flash ther self animation to help the cognitive abilities of students. Methods of system design using UML (Unified Modeling Language) teaching methods that made prioritize ease in conveying the material such as animal identification, letter recognition, number recognition, addition and subtraction using animation attraktif simple and easy to understand. With the Application Media Student Learning Kindergarten to use Flash animation that talks about learning to count and comes with the introduction of number and letter recognition. is expected to attract the attention of kindergarten children to learn to count, can add to the appeal of student learning and motivate student TK TK more active in understanding the subject matter and also assist teachers in teaching and learning. Keywords: learning media, numeracy and flash animation ABSTRAKSI Pembelajaran Siswa Taman Kanak-Kanak umumnya masih menggunakan Alat Peraga dimana biasanya Siswa dikenalkan terlebih dahulu benda yang ada disekitar Sekolah berdasarkan Tema yang ada, kemudian siswa diperkenalkan Angka, Huruf dan kemudian belajar berhitung. Berdasarkan adanya masalah di Taman Kanak-Kanak tentang proses pembelajaran masih monoton yaitu guru menerangkan pengenalan angka, huruf dan belajar berhitung hanya melalui buku. Sehingga siswa mudah bosan dan kurang memahami mengenai pengenalan angka, huruf dan belajar berhitung. Serta siswanya banyak dan gurunya sedikit sehingga siswa ada yang bermain sendiri Oleh karena itu diperlukan Media Pembelajaran Siswa Taman Kanak-Kanak Menggunakan Animasi Flash untuk membantu kemampuan kognitif Siswa. Metode perancangan sistem menggunakan UML (Unified Modelling Language) metode pembelajaran yang dibuat mengedepankan kemudahan dalam menyampaikan materi seperti pengenalan binatang, pengenalan huruf, pengenalan angka, penjumlahan dan pengurangan sederhana menggunakan animasi yang attraktif dan mudah dipahami. Dengan adanya Aplikasi Media Pembelajaran Siswa Taman Kanak-Kanak menggunakan Animasi Flash yang membahas tentang Pembelajaran berhitung serta dilengkapi dengan pengenalan angka dan pengenalan huruf. diharapkan bisa menarik perhatian siswa TK untuk belajar berhitung, dapat menambah daya tarik belajar siswa TK serta memotivasi siswa TK lebih giat lagi dalam memahami materi pelajaran dan juga membantu guru dalam kegiatan belajar mengajar. Kata Kunci : media pembelajaran, berhitung dan animasi flash